Pengaruh Mekanisme Bonus dan Multinationality terhadap Keputusan Transfer Pricing pada Perusahaan Manufaktur di Bursa Efek Indonesia - Isra Maulina; Almira Keumala Ulfah; Heny Rofizar; Husni Kamal; Muhammad Syafril Nasution (Mahesa Research Center, 2021)
This article aims to examine and analyze the Effect of Bonus Mechanisms, and Multinationality on Transfer Pricing Decisions in Manufacturing Companies Listed on the IDX for the 2016-2018 period. The population used in this study were 154 manufacturing companies listed on the Indonesia Stock Exchange, and the sample was taken using a purposive sampling method, namely 25 companies. The data collection technique used in this research is secondary data. Based on the analysis that has been done, the results show that H1 is rejected. This means that the bonus mechanism has no effect on transfer pricing. Bonuses are not a motivator for the board of commissioners to do transfer pricing, because basically the board of commissioners before doing transfer pricing must first consider the risk compared to the bonus. H2 is rejected. That is, multinationality has no effect on transfer pricing. This means that not all multinational companies can reduce their taxes by doing transfer pricing, this is because, if the company has a subsidiary in a part of the country that has high taxes, the multinational company cannot reduce its taxes with this alternative.